Does specialist physician supply affect pediatric asthma health outcomes? - Guido Filler; Tom Kovesi; Erik Bourdon; Sarah Ann Jones; Laurentiu Givelichian; Cheryl Rockman-Greenberg; Jason Gilliland; Marion Williams; Elaine Orrbine; Bruno Piedboeuf; The Paediatric Chairs of Canada Mark Bernstein (BMC, 2018)
Abstract Background Pediatrician and pediatric subspecialist density varies substantially among the various Canadian provinces, as well as among various states in the US. It is unknown whether this variability impacts health outcomes. To study this knowledge gap, we evaluated pediatric asthma admission rates within the 2 Canadian provinces of Manitoba and Saskatchewan, which have similarly sized pediatric populations and substantially different physician densities. Methods This was a retrospective cross-sectional cohort study. Health regions defined by the provincial governments, have, in turn, been classified into "peer groups" by Statistics Canada, on the basis of common socio-economic characteristics and socio-demographic determinants of health. To study the relationship between the distribution of the pediatric workforce and health outcomes in Canadian children, asthma admission rates within comparable peer group regions in both provinces were examined by combining multiple national and provincial health databases. We generated physician density maps for general practitioners, and general pediatricians practicing in Manitoba and Saskatchewan in 2011. Results At the provincial level, Manitoba had 48.6 pediatricians/100,000 child population, compared to 23.5/100,000 in Saskatchewan. There were 3.1 pediatric asthma specialists/100,000 child population in Manitoba and 1.4/100,000 in Saskatchewan. Among peer-group A, the differences were even more striking. A significantly higher number of patients were admitted in Saskatchewan (590.3/100,000 children) compared to Manitoba (309.3/100,000, p < 0.0001). Conclusions Saskatchewan, which has a lower pediatrician and pediatric asthma specialist supply, had a higher asthma admission rate than Manitoba. Our data suggest that there is an inverse relationship between asthma admissions and pediatrician and asthma specialist supply.